Histological type-specific prognostic factors of cervical small cell neuroendocrine carcinoma, adenocarcinoma, and squamous cell carcinoma - Suthida Intaraphet (2018)
Background: The study aimed to determine the prognostic impact of clinical and pathological factors on survival among patients with small cell neuroendocrine carcinoma (SNEC), adeno-carcinoma (ADC), and squamous cell carcinoma (SCC). Methods: Eligible participants were all patients with histologically confirmed cervical cancer treated at Chiang Mai University Hospital between 1 995 and 2 011. We included all patients with SNEC and randomly enrolled patients with ADC and SCC. We used competing-risk regression analysis to examine the risk of cancer-related death by histological type. Results: We included 1 30 (6.2%) women with SNEC, 3 46 (16.4%) with ADC, and 1,632 (77.4%) with SCC. Age>60 years (hazard ratio [HR] 4.9, 95% confidence interval [CI] 2.0-12.0) and lymph node involvement (HR 3.0, 95% CI 1.2-7.4) were prognostic factors among surgically-treated patients with SNEC. Deeper stromal invasion (HR 3.6, 9 5% CI 1.6-8.3) was a prognostic factor in patients with SCC. In patients with advanced SNEC, age>60 years had a strong prognostic impact (HR 2.6, 95% CI 1.0-6.5) while the International Federation of Gynecology and Obstetrics stages III and IV were prognostic factors for patients with advanced stage ADC (HR 2.9, 95% CI 2.0-4.4 and HR 4.5, 95% CI 2.6-7.9, respectively) and SCC (HR 1.7, 95% CI 1.4-2.0 and HR 3.7, 95% CI 2.8-4.9, respectively) compared with the International Federation of Gynecology and Obstetrics stage IIB. Conclusion: Clinical and pathological prognostic factors in cervical cancer differed according to histological type. Taking the important prognostic factors for each histological type into consideration may be beneficial for tailored treatment and follow-up planning. © 2014 Intaraphet et al.